Quality, Usability, and Potential Effectiveness of Self-Learning Modules in Social Studies - Doria, Jechie P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The research study was intended to make an evaluation of the quality (contents, format presentation and organization, and usability) and effectiveness of Self-Learning Modules (SLMs) for Secondary Social Studies teachers of secondary schools in Zone 3, Division of Zambales. The perceptions and insights were solicited from the teacher - participants. The study was conducted during the Second Quarter of the school year 2020-2021. This study employed a descriptive research method with the survey questionnaire as the research instrument. The statistical treatment of this study utilized descriptive statistical tools. ANOVA and Pearson r are the inferential statistics used.The findings of the study revealed that the quality of Self-Learning Modules (SLMs) for Secondary Social Studies Program was very Satisfactory in terms of format, content and presentation and organization. However, the SLM was Satisfactory in Usability. The academic performance of the junior high school students in social studies was proficient in their pre-test and advanced in the post-test. Results also revealed that there is no significant difference on the perception of the respondents to the Quality of SLM for the Secondary Social Studies Program in terms of content, format, presentation and organization and usability. There is significant difference on the pre-test and post-test performances of the students in Social Studies (Araling Panlipunan) lessons. There is no significant relationship/correlation between the Quality and Effectiveness of the Self-Learning Modules (SLMs) in terms of content, format and presentation and organization.